Effect of Statin Therapy on Fibrous Cap Thickness in Coronary Plaques Using Optical Coherence Tomography: A Systematic Review and Meta‐Analysis. (21st October 2015) - Zheng, Guian; Chen, Jiandong; Lin, Chunyi; Huang, Xiaohong; Lin, Jinxiu
Abstract : Objectives: We conducted a systematic review and meta‐analysis to evaluate the effect of statin therapy on coronary fibrous cap thickness (FCT) as assessed by optical coherence tomography (OCT) and the relationship between FCT and traditional coronary risk factors. Background: Increasing evidence has shown that statin therapy results in a marked increase in coronary FCT. However, the relationship between this increase in FCT and the lipid profile has not been clearly elucidated. Methods: A literature search of PubMed, Embase, the Cochrane Library, and Web of Science up to March 17, 2015 was performed. Studies providing data on FCT using OCT at baseline and follow‐up in patients receiving statin therapy were included. Weighted mean difference (WMD) with a random‐effects model was used. Results: Six OCT studies were included. The FCT in coronary plaques was significantly increased after statin therapy (WMD: 58.79 μm, 95% CI 33.82–83.76 μm, P < 0.001). When compared with the placebo group, the increase in FCT was also greater in the statin group (WMD: 72.28 μm, 95% CI 44.97–99.58 μm, P < 0.001). Meta regression analysis demonstrated no significant correlations between the increase in FTC and the changes in total cholesterol, low‐density lipoprotein cholesterol and high‐density lipoprotein cholesterol levels during follow‐up. Similarly, there were no significant correlations between the increase in FCT and age, male gender, hypertension, diabetes, and smoking. Conclusions: Statin therapy induced a significant increase in coronary FCT evaluated by OCT. This increase in FCT was independent of traditional coronary risk factors including the lipid profile. (J Interven Cardiol 2015;28:514–522)